Forming Learners Through Citizenship Education to Recognise and Counter Lawlessness in their Surroundings - Van der Walt, Johannes L. (Koers, 2024)
Due to various conditions, countries such as Venezuela, Nigeria, and South Africa suffer from lawlessness (disregard of norms and rules of society) today, threatening their social fabric. It is contended on the basis of the situation in South Africa that citizenship education is arguably a suitable vehicle (in combination with, for instance, religion education, moral education, and forgiveness education) for offering tolerance, forgiveness, hospitality, and reconciliation education in schools, all of these as means for counteracting lawless (deviant, errant) behaviour. Thus far, reflection on citizenship education has, however, been characterised by conceptual uncertainty, controversy, and a wide range of applications in practice. The paper reports on theoretical interpretive-constructivist research. This research is aimed at the question of how citizenship education could be employed to form (equip, educate) young people so that they can be able to display morally justifiable behaviour and recognise and counteract lawlessness wherever they encounter it in their lifeworld.